Analisis Pembelajaran PKn dalam Menciptakan Toleransi di Sekolah - Armi Alzzaini Alkautzhar; Indah Syifa Virani; Nazhifatun Zulfa Nabilah; Dita Lutfiah; Rama Wijaya Abdul Rozak; Nisrina Nurul Insani (Jurnal Ilmiah Pendidikan Holistik (JIPH), 2023)
Tolerance attitudes of students in schools are now starting to experience a decline with so much rejection of differences in many aspects of life. The purpose of this research is to find out whether Citizenship Education is able to create an attitude of tolerance in students at school. In conducting our research we used a descriptive qualitative method where our main focus in collecting data was interviewing three teachers of civics education at the senior high school level. The results of the study show that the Citizenship Education Subject has been able to create an attitude of tolerance in students towards their friends at school, especially during discussions in class. Although in the process of practice it is often faced with many obstacles both from the attitude of students and the surrounding environment.